Pursuing Civilian Control Over the Military. Issue 3 (July 2019) - Travis, Donald S.
This essay is responding to Dr. Ionut Popescu's review of the article "Saving Samuel Huntington and the Need for Pragmatic Civil-Military Relations." He challenges the pragmatist outlook by questioning its usefulness to "manage relations between the military and its civilian superiors in a democracy such as the United States." Based on the concerns of Morris Janowitz regarding military relations, three assertions are made in defense of the pragmatic approach. First, the choice between "professional versus civilian supremacy" for making crucial decisions during wartime is misleading because it is based on obsolete thinking from the twentieth-century Cold War. Second, types of wars waged are determined by complex and provisional decision-making processes amid political struggle. Third, Huntington's civil–military theory wrongly maligns the word "politics" by distorting its meaning and purpose. Politics is a natural process and an essential feature of democracy.